Self-powered multifunctional body motion detectors based on highly compressible and stretchable ferroelectrets with an air-filled parallel-tunnel structure. (1st December 2022) - Ma, Xingchen; Chen, Xin; Xiang, Xinhao; Zhang, Fei; Zhao, Yanjun; Wang, Fayang; Mu, Xiaojing; Dai, Ying; He, Pengfei; Zhang, Xiaoqing
Abstract: The new kind of ferroelectret electroactive polymers for flexible film sensors represent an attractive opportunity for self-powered wearable devices, which could offer sustainable and convenient health care services for people without the problem of energy supply. However, due to the mechanical heterogeneity, obtaining ferroelectrets with both a high longitudinal and transverse piezoelectric response is still a great challenge, which limits its multifunctional sensing application, especially in body motion tracking. Herein, we develop an air-filled parallel tunnel ferroelectret-based self-powered body motion detectors. Ascribed to the high mechanical compression and tensile properties of the specially designed parallel tunnel void structure and excellent charge storage stability of the fluorinated polyethylene propylene (FEP) electret film, these laminated films exhibit many fascinating merits, including ultrahigh longitudinal piezoelectric response (piezoelectric coefficient of 6200 pC/N, pressure sensitivity of 1950 pC/kPa), wide pressure detection range (0.03–62 kPa), remarkable transverse piezoelectric response (tensile sensitivity of 1600 pC/mm), long-term durability (1, 08, 0000 cycles), and superior friction force detection capability. This is the first work, to our knowledge, that ever use one kind of piezoelectric mechanism in a single ferroelectret-based sensor to achieve longitudinal stress, transverse stress, and tangential friction force sensing. Furthermore, on the basis of such sensors and machine learning algorithms, we designed an intelligent gesture recognition system for future human-machine interaction applications. Looking forward, our material design methodologies offer an approach to the self-powered flexible multifunctional sensor with great prosperity in household healthcare, smart mobile medical electronics, and humanoid robots. Graphical Abstract: A novel self-powered flexible multifunctional sensor design strategy enabled longitudinal stress, transverse stress, tangential friction force sensing utilizing one kind of piezoelectric mechanism in a single ferroelectret-based sensor. Furthermore, on the basis of such sensors and machine learning algorithms, we designed an intelligent gesture recognition system for future human-machine interaction applications. ga1 Highlights: Multi-dimensional force sensing was achieved in a single sensor by using one kind of piezoelectric mechanism. We designed an intelligent gesture recognition system for future human-machine interaction applications. Our material design methodologies offer an approach to the multifunctional sensor with prosperity in household healthcare.